Single Center Experience With Robotic Kidney Transplantation for Recipients With BMI of 40 kg/m2 Or Greater: A Comparison With the UNOS Registry. Issue 1 (January 2017) - Garcia-Roca, Raquel; Garcia-Aroz, Sandra; Tzvetanov, Ivo; Jeon, Hoonbae; Oberholzer, Jose; Benedetti, Enrico
Abstract : Background: Obesity represents a barrier to kidney transplantation, but the increasing prevalence among renal failure patients has forced some centers to carefully consider such candidates. Morbidly obese patients may be at increased risk of delayed graft function, higher postoperative complications, and inferior graft outcomes. Nevertheless, mortality on the waiting list remains significantly higher than after transplant. We have applied minimally invasive surgery to perform kidney transplant in individuals with body mass index (BMI) of 40 kg/m 2 or greater. We compared our results to the national United Network of Organ Sharing database. Methods: The United Network of Organ Sharing registry was reviewed for adult living donor kidney transplant recipients with BMI of 40 kg/m 2 or greater performed from September 2009 to December 2014. We compared transplants performed with robotic technique (RKT) versus patients performed with open surgery at all US centers including our own (open kidney transplant). Subgroup analysis in patients with BMI of 45 kg/m 2 or greater was conducted. We compared outcomes including patient and graft survival, renal function, and technical complications. Results: Robotic kidney transplantation group had a significantly higher mean BMI overall. The 1-year patient and graft survival rates were similar between groups. Renal function was also similar at 6, 12, and 36 months. Thrombosis caused 1.3% of the graft losses in open kidney transplant and 0% in the RKT group. Interestingly, 52.8% of the overall experience in patients with BMI of 45 kg/m 2 or greater was performed with the robotic technique. Conclusions: Robotic surgery offers similar patient and graft survivals with comparable renal function to open technique. Robotic kidney transplantation permits transplantation in extreme BMI categories without additional technical complications. Further studies are required to establish the role of RKT for obese candidates but preliminary data are encouraging. Abstract : Transplants performed with robotic technique (RKT) offer similar patient and graft survival with comparable renal function to open technique. Although the data is preliminary, RKT permits transplantation in extreme BMI categories (BMI=40kg/m2) without additional technical complications.